Comparison of patient flow and provider efficiency of two delivery strategies for HPV-based cervical cancer screening in Western Kenya: a time and motion study - Easter Olwanda; Jennifer Shen; James G. Kahn; Katelyn Bryant-Comstock; Megan J. Huchko (Taylor & Francis Group, 2018)
Background: Improving patient flow and reducing over-crowding can improve quality, promptness of care, and patient satisfaction. Given low utilization of preventive care in low-resource countries, improved patient flows are especially important in these settings. Objective: Compare patient flow and provider efficiency between two cervical cancer screening strategies via self-collected human papillomavirus (HPV). Methods: We collected time and motion data for patients screened for cervical cancer in 12 communities in rural Migori County, Kenya as part of a larger cluster randomized trial. Six communities were randomized to screening in community health campaigns (CHCs) and six to screening at government clinics. We quantified patient flow: duration spent on each active stage of screening and wait times, and the number of patients arriving at CHCs and clinics each hour of the day. In addition, for four CHCs, we collected time and motion data for providers, and measured provider efficiency as a ratio of active (service delivery) time to total time spent at the clinic. Results: Total duration of screening visits, at CHCs and clinics was 42 and 87 minutes, respectively (p < 0.001 for difference). Total active time lasted longer at CHCs, with a mean of 28 minutes per patient versus 15 minutes at clinics, largely due to differences in duration for group education (p < 0.001). Wait time for registration at clinics was 36 minutes, explaining most of the difference between settings, but sometimes incorporated other health services. Conclusions: There is a substantial difference in patient flow at clinics compared to CHCs. Shorter duration at CHCs suggests that the model is favorable for patients in limiting time spent on screening. Future cervical cancer screening programs designed for scale-up should consider how this advantage may enhance satisfaction and uptake. For clinic-based screening programs, efforts could be made towards reducing registration wait times.